Development of Wireless Sensor Network for Monitoring Air Temperature and Soil Moisture on Crops - Wulandari Wulandari (IPTEK Journal of Proceedings Series, 2014)
Crops including the types of plants that can be grown in dry areas. In dry areas as development land crops, humans attempt to make this by doing irrigation. However, if the amount of water given too much will cause the plants rot and crop failures. Therefore, necessary irrigation system that can be monitored periodically by the farmers to avoid such problems. Wireless sensor networks can be used to monitor land crops. By using the temperature and humidity sensors and soil moisture sensors, soil will be monitored regularly every hour. Data resulting from sensor readings are sent to the database using the GPRS network. The results showed that the prototype of a wireless sensor network on crops have been successfully developed.